The Experience Left by COVID-19 - Sterin Prync, Aída E. (Revista del Hospital Italiano de Buenos Aires, 2024)
A comment reflecting on the COVID-19 pandemic, highlighting its global impact and the lessons learned. It emphasizes the cooperation between scientists, companies, and governments, particularly in biotechnology, to address the crisis. Additionally, it discusses the lasting effects of COVID-19, such as post-traumatic syndrome, and the importance of leveraging these advancements for future emergencies.